Gene signature driving invasive mucinous adenocarcinoma of the lung - Minzhe Guo; Koichi Tomoshige; Michael Meister; Thomas Muley; Takuya Fukazawa; Tomoshi Tsuchiya; Rebekah Karns; Arne Warth; Iris M Fink‐Baldauf; Takeshi Nagayasu; Yoshio Naomoto; Yan Xu; et al. (EMBO Molecular Medicine)
Abstract Though invasive mucinous adenocarcinoma of the lung (IMA) is pathologically distinctive, the molecular mechanism driving IMA is not well understood, which hampers efforts to identify therapeutic targets. Here, by analyzing gene expression profiles of human and mouse IMA, we identified a Mucinous Lung Tumor Signature of 143 genes, which was unexpectedly enriched in mucin‐producing gastrointestinal, pancreatic, and breast cancers. The signature genes included transcription factors FOXA3, SPDEF, HNF4A, mucins MUC5AC, MUC5B, MUC3, and an inhibitory immune checkpoint VTCN1/B7‐H4 (but not PD‐L1/B7‐H1). Importantly, induction of FOXA3 or SPDEF along with mutant KRAS in lung epithelium was sufficient to develop benign or malignant mucinous lung tumors, respectively, in transgenic mice. FOXA3 and SPDEF induced MUC5AC and MUC5B, while HNF4A induced MUC3 in human mucinous lung cancer cells harboring a KRAS mutation. ChIP‐seq combined with CRISPR/Cas9 determined that upstream enhancer regions of the mucin genes MUC5AC and MUC5B, which were bound by SPDEF, were required for the expression of the mucin genes. Here, we report the molecular signature and gene regulatory network driving mucinous lung tumors.